Processing Characterization of Sisal/Epoxy Prepregs - Silva, Sayra O.; Teixeira, Linconl A.; Gontijo, Alexandre Bahia; Luz, Sandra M. (Journal of Research Updates in Polymer Science, 2021)
Quality control to obtain composite laminates is frequently applied to synthetic fibers/epoxy prepregs. The gel time test, resin, volatiles and fiber content, drape measurement and tack tests together with water absorption capacity are methods currently employed. However, for natural fibers prepregs there is a gap in the literature, which makes their application difficult. Thus this work will investigate sisal fibers, which have low cost, high biodegradability and low specific weight, following the common methods to manufacture composites from natural fibers/epoxy prepregs. First, the prepregs were prepared by hand lay-up, aligning the fibers with epoxy, keeping 15% by weight content of fiber. After the quality control characterization, 3 mm thickness composite was prepared by using a press, and tensile tests and scanning electron microscopy (SEM) were applied. As a result, the resin fraction values and the solid content of the matrix showed little variation between the different samples. The natural fibers prepregs absorbed water quickly in the initial stage until reaching the saturation level. The NaOH-treated sisal/epoxy prepreg had a tension of 71.06 ± 8.28 kPa for the tack test and tensile strength of 69.24 ± 11.69 MPa. Finally, the NaOH-treated sisal 15 wt%/epoxy resulted in composites with a better performance than the neat epoxy resin. There was good adhesion between the fibers and matrix, as confirmed by SEM and mechanical tests.